If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 8 = -16 + -9 Reorder the terms: 8 + 3x = -16 + -9 Combine like terms: -16 + -9 = -25 8 + 3x = -25 Solving 8 + 3x = -25 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8' to each side of the equation. 8 + -8 + 3x = -25 + -8 Combine like terms: 8 + -8 = 0 0 + 3x = -25 + -8 3x = -25 + -8 Combine like terms: -25 + -8 = -33 3x = -33 Divide each side by '3'. x = -11 Simplifying x = -11
| x^2-8+16=3x-12 | | 290=x+273.15 | | -9c+5+7c=-3c+10 | | 4(c)*2=4c*2 | | 15xy=-75 | | x^2-8x-3x=-12-16 | | -9=z | | 6y-20=15y-30 | | (4c)*2=8c*2 | | -24x^2+24=0 | | 5x+5=23+2 | | 9x^2-1+(6x^2)(x-4)=0 | | 4x=12x-72 | | 8w-4wz= | | -37=5+7x | | x+2=9x-8 | | 7d+d-4d-5d=6d | | -1+8.4+3= | | x^2+10x+12=36 | | 3x+3=2x+5 | | 2d+4d=4-d | | 3x-3=4x-7 | | 4+3x-3=2x-4 | | 4.2(-1)(-2)= | | 4x-10=8-(3+x) | | 2x+3x=189-4 | | 8u-2=54 | | 5(y+6)=60 | | y+5=7y-25 | | 0.5(10a-15)=3-2a | | -b=-4 | | 52-7x=20x+19 |